POLITIK IDENTITAS DALAM PEMILIHAN UMUM 2019 (Terpilihnya Haji Bambang Santoso sebagai DPD RI Dapil Bali) - Ayuningsih, Ni Made; Erviantono, Tedi; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika, 2022)
The purposeeof this researchhis to identify the issue of identity politics in the 2019 general election, specifically in the DPD RI legislative. Manuel Castells theory of identity politics is used to frame this study. The research method is a descriptive method with a qualitative approach. Respondents were selected by purposive technique. The result of this study is the existence of identity politics in the form of religious issues was employed in the election campaign for the DPD RI in the Bali Dapil by the candidate for the DPD RI Bali, namely Haji Bambang Santoso is the only Muslim DPD RI candidate in the Bali electoral district. With the tagline